EL MÉTODO DE PROYECTOS Y SU RELACIÓN CON EL APRENDIZAJE DE BIOLOGÍA GENERAL, EN EL TERCER SEMESTRE DE LA CARRERA DE BIOLOGÍA, QUÍMICA Y LABORATORIO DE LA FACULTAD DE CIENCIAS DE LA EDUCACIÓN, HUMANAS Y TECNOLOGÍAS, PERIODO SEPTIEMBRE 2013-MARZO 2014. - Sagñay Valente, Norma Isabel (2014)
Research on the project method and its relationship with learning General Biology seeks to establish a logical ordering of the steps required to realize the most efficient , effective and quality in the process of teaching and learning how to do there documents as sources of query that is vital to this investigation as a reference in magazines , books , brochures, etc. ; because we have the necessary economic resources needed time with oneself. This project saves and indirect beneficiaries originality and professionalism of the research and the impact on teachers and students of the National University of Chimborazo, direct beneficiaries of this project, students in the third semester of studies in Biology, Chemistry and Laboratory all people related to education in general. Therefore , it is determined an enabling environment for the development of planned activities , motivating the interest and participation of students; thus methods projects contribute in the integral formation of the students , since it allows to develop different aspects , academic and emotional , including their creative abilities and participation . This work was performed to support learning and knowledge within General Biology and serve as the basis for the formation of human beings, students and the carreara third semester of Biology, Chemistry and Laboratory Riobamba canton being the beneficiaries. In the present investigation , it was established aimed at determining the influence of project methodologies related to good living , improving skills development for children learning through project work .